Swedish - Finnish glossary: caring professions - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with caring professions. Published in Kieliviesti 2/2007. Contains approximately 140 entries. 2007.

Svensk-sverigefinsk ordlista med yrken inom vård och omsorg. Publicerades i Kieliviesti 2/2007. Innehåller ca 140 ord. 2007.
Svensk-finsk ordlista: vårdyrken
Keywords: Health Occupations; Vårdyrken; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur